(فعالية الطريقة الجزئية لترقية مهارة القراءة (دراسة تجريبية: THE EFFEVTIVENESSOF PARTIAL METHOD TO IMPROVE READING SKILL (AN EXPERIMENTAL STUDY) - Irmasani Daulay (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2020)
Abstract: This study aims to determine the effectiveness of the Synthesis Method to Improve Students' Reading Ability in MAN 1 Pekanbaru. This study is an experimental research, which is a research method used to look for the effect of certain treatments on others under controlled conditions. Using the experimental design of the Control Group Pretest-Posttest. Based on observations obtained 92% means